FACTORS THAT AFFECT READING COMPREHENSION: A VISION SUPPORTED BY DIFFERENT PERSPECTIVES - Isadora Muñoz Corté; Yorly Milena Rojas Angarita; Luz Magally Moreno Rodrígue (DIALÉCTICA, 2025)
his dissemination article takes a tour of the different positions and perspectives regarding the factors that affect the reading comprehension of children and young people of school age, beginning by presenting data that show the current reality in Colombia in terms of the level it has compared to other countries, to highlight the importance of the topic. Once the bibliographic review and theoretical contributions are made, the information is integrated to synthesize it, in order to better understand these factors. It is concluded that in Colombia there are needs to be covered, taking into account that the factors come individually and collectively and that there are agents given by the geographical location of the subject and whether or not access to materials and activities aimed at the development of reading comprehension. Countries are taken as an example in which their citizens take advantage of their leisure time for reading and people have easy access to books.